Internal Control System Analysis of Cash Flow - Riyanto, Didik; Oktavia, Puja; Jefriyanto, Jefriyanto (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2022)
This study aims to determine the extent to which the internal control system for cash receipts and disbursements is carried out by the Al-Hafidz DAPM UPK in carrying out its activities in order to achieve its goals. The method used in this research is qualitative research, with flowchart data analysis techniques, namely by pictorial analysis techniques used to explain the procedures that occur briefly and clearly, and descriptively, namely by first collecting data, classifying and interpreting data so that it can provide a clear picture of the problem under study. In collecting data using observation techniques, interviews, questionnaires and documentation, where the data taken is primary data in the form of evidence of records or historical reports that have been arranged in published and unpublished archives. The results of this study indicate that the internal control system for cash receipts and disbursements at UPK DAPM Al-Hafidz has been running well, but is not fully in accordance with the five components of internal control according to COSO theory. Four components are appropriate, namely the control environment, risk assessment, information and communication, and monitoring, while one component, namely control activities, is not appropriate.